Islamic banking and finance - Molyneux, Philip (Henry Stewart Talks, 2014)
Islamic banking, Islamic finance, What is Islamic banking, Principles of Islamic banking, Principles of Islamic finance, Shariah principles, Size of Islamic banking, Top Islamic banks- Islamic equity, Islamic funds, Islamic wealth management, Islamic bonds